2019
DOI: 10.1108/ilt-01-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adhesion strength on cavitation erosion resistance of diamond-like carbon coating

Abstract: Purpose The disbonding of DLC coating is a main failure mode in the high-speed cavitation condition, which shortens the service life of the bearing. This study aims to investigate influence of adhesion strength on cavitation erosion resistance of DLC coating. Design/methodology/approach Three DLC coatings with different adhesion strengths were grown on the 304 steel surfaces by using a cathodic arc plasma deposition method. Cavitation tests were performed by using a vibratory test rig to investigate the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The high compressive stress of hard DLC coatings often leads to poor adhesion with tool steel substrates, limiting its practical applications. Furthermore, the plastic deformation and fracture of DLC coatings have been attributed by Cheng et al [41] to higher residual stress and poorer adhesion strength, impacting the cavitation erosion resistance of DLC coatings. Figure 10 displays microscopy images that reveal the scratch test grooves.…”
Section: Adhesion Testsmentioning
confidence: 99%
“…The high compressive stress of hard DLC coatings often leads to poor adhesion with tool steel substrates, limiting its practical applications. Furthermore, the plastic deformation and fracture of DLC coatings have been attributed by Cheng et al [41] to higher residual stress and poorer adhesion strength, impacting the cavitation erosion resistance of DLC coatings. Figure 10 displays microscopy images that reveal the scratch test grooves.…”
Section: Adhesion Testsmentioning
confidence: 99%
“…Cheng et al reported that the cavitation erosion resistance of these films is highly related with their micro defects and adhesion strengths with their substrates. [9,10] Gerke et al demonstrated that different substrate materials can influence the cavitation erosion behaviors of DLC films by affecting their reversible deformation and the film/substrate adhesion strengths. [11] Kanda et al studied the erosion of the fluorinated DLC films exposed to soft X-rays and found that the radiation can cause the uniform decrease in fluorine composition from film surface to substrate.…”
Section: Introductionmentioning
confidence: 99%